New spectroscopic and diffraction data to solve the vanadium-doped zircon pigment conundrum. Issue 15 (December 2018) - Ardit, Matteo; Cruciani, Giuseppe; Di Benedetto, Francesco; Sorace, Lorenzo; Dondi, Michele
Abstract: The literature on V-doped zircon pigments offers a puzzling situation with unanswered questions about the origin of turquoise colour. In this study, new diffraction (XRPD) and spectroscopic (EPR, EAS) data were obtained on four industrial pigments, whose vanadium content is much higher than samples from previous investigations. Both EPR features and XRPD results indicate the occurrence of tetrahedrally-coordinated V 4+ at the zircon interstitial site 16 g . EPR spectra at 5 K exhibit a structured multiplet attributed to isolated V 4+ ions and an exchange-narrowed line resulting by clustering of V 4+ ions. The intensity of optical bands is stronger in samples affected by V 4+ clusters. However, the turquoise colour stems from the window of transmitted green-bluish light, which depends on both the tail of the main optical band ( 2 B ⟵  2 A) and the onset of charge transfer phenomena. Small variations in these two bands readily turn into a chromatic shift from light blue to green.